Treatment of cerebral glioblastoma-caused bruxism with mirtazapine: a case report - Mohsen Khosravi (JA Clinical Reports, 2020)
Abstract Background Bruxism refers to grind or gnash the opposing rows of upper and lower molar teeth. It is important to treat bruxism as a factor that can influence sleep quality, quality of life, and mental status in patients with malignancy. Case presentation A 41-year-old male developed bruxism secondary to cerebral glioblastoma. l-dopa, gabapentin, clonazepam, clonidine, baclofen, buspirone, or propranolol were not effective. Mirtazapine, prescribed for side effects of chemotherapy, was effective for bruxism, which was disappeared within 3 weeks. Conclusions Mirtazapine was effective for treating bruxism as well as chemotherapy complications.